Efficient and sustainable design for demand-supply and deployment of waste heat and cold energy recovery in marine natural gas engines. (20th November 2020) - Ouyang, Tiancheng; Su, Zixiang; Wang, Feng; Jing, Biyu; Huang, Haozhong; Wei, Qifeng
Abstract: Considering the impending global energy crisis and increasing environmental pollution, and the rapid growth of the shipping industry, there is an urgent need for efficient, clean, and sustainable technology to increase the energy efficiency and profitability of the shipping industry. In this paper, we propose an integrated waste heat and cold energy recovery system for marine natural gas engines that can conserve energy, reduce pollution, and satisfy the dynamic daily energy demands of a ship. The accuracy of the model is evaluated by comparing it with results of previous studies. The sensitivity of various parameters on each subsystem is analysed, and the relationship between the mass flow and the parallel system is discussed. After determining the optimum operating conditions, the thermodynamic and economic performance of each subsystem and the combined system are analysed. The results indicate that the initial investment cost of the combined system can be recovered in 6.976 years. The fuel savings and reduction in carbon dioxide emissions are 38.55 kg/h and 52.08 kg/h, which proves that the proposed system can achieve excellent economic performance and emission reductions. Compared with the original engine, the net power production and thermal efficiency of the proposed system are 214.5 kW and 5.14% higher. The proposed achieves energy conservation and pollution reduction and satisfies the dynamic energy demands of the ship; it is also economically viable and fills the gap of multiform utilisation of cold energy in waste heat recovery. Graphical abstract: Image 1 Highlights: A design of integrated waste heat and cold recovery, deployment and supply is proposed. By combining parallel system and energy storage device to achieve dynamic energy demand. Considering the use of cold energy to purify the domestic sewage produced on board. The positive effect of quantitative combined system on natural gas engine. The power and thermal efficiency are improved by 214.5 kW and 5.14%, respectively.